The influence of double flask processing in occlusal plane when a couple of dentures are processed in occlusal position - Célia Marisa Rizzatti-Barbosa; Vicente de Paula Prisco da Cunha; Leonardo Marchini; Margarete Cristiane Ribeiro (Universidade Estadual de Campinas, 2015)
Equilibrate occlusion system is an important goal in oral rehabilitation. This occlusal scheme is established when the denture teeth are placed in the plane of orientation, and could be changed by alterations related to polymerization resin process. The aim of this research was to evaluate vertical occlusal plane changes after processing, using two types of flasks: a conventional single flask (C), and a flask designed to process upper and lower denture simultaneously in occlusal position (HH). Twenty double dentures (upper and lower) were reproduced by a maxilla and mandible master metallic models simulating edentulous upper and lower couple arches. Four metallic apparatus simulating molar and canine cusps were placed on plane of orientation at molar and canine positions of all dentures. The Group I couple samples were processed individually using single conventional flask (C), and the ten couple samples of Group II were polymerized using a flask designed to process upper and lower denture simultaneously, in optimal positioning teeth (HH). A linear measurement instrument measured the distance between metallic top of each cusps and the cast bone before and after dentures processing. The data were analyzed by z test at 95% confidence level, and made possible to verify that the modification occurred in Group I were aleatory, with prevalence of negative results to upper and lower dentures. In Group II samples was observed that occurred regulars movements of metallic patterns in function of their antagonists, showing homogeneous alterations on patterns. Was observed statistical difference between group I and Group II samples, were Group II exhibited better results of occlusion teeth accuracy after processing than Group I samples